IBS Patients' Treatment Expectancy and Motivation Impacts Quality of the Therapeutic Alliance With Provider: Results of the IBS Outcome Study - Lackner, Jeffrey M; Quigley, Brian M; Radziwon, Christopher D; Vargovich, Alison M (Journal of clinical gastroenterology, 2021)
In the absence of a satisfactory medical or dietary treatment, the quality of the therapeutic alliance between irritable bowel syndrome (IBS) patients and their provider is deemed critical to managing refractory IBS. Surprisingly, little research has been conducted on the nature of the therapeutic alliance, factors that influence it, or practical strategies to improve it. This study sought to identify actionable variables that impact therapeutic alliance in patients with refractory IBS. Subjects included a total of 436 Rome III-diagnosed IBS patients (80% female, mean age=41.39 y) who completed a battery of clinical measures at the beginning of the acute treatment phase of an National Institutes of Health (NIH) behavioral trial. Pretreatment candidate predictor variables were organized into 4 categories: sociodemographic, extraintestinal, interpersonal, clinical (eg, symptom severity, pain intensity), cognitive (eg, treatment motivation, expectancy for improvement). Alliance was assessed by patient and clinician-rated measures of the Working Alliance Inventory after first treatment session. Patient reports of alliance were most strongly and consistently predicted by patient access to interpersonal support [β=0.16; 95% confidence interval (CI)=0.07-0.25], motivation for IBS symptom improvement (β=0.12; 95% CI=0.02-0.21), and expectancy of IBS symptom improvement (β=0.35; 95% CI=0.25-0.44). Therapist ratings of alliance also were predicted by patient expectancy of IBS symptom improvement (β=0.16; 95% CI=0.05-0.26). When managing IBS, a focus on dynamic factors of treatment motivation, social support, and treatment expectancy may be useful in improving the quality of the therapeutic alliance between patient and clinical gastroenterologist.